2021
DOI: 10.1097/gox.0000000000003945
|View full text |Cite
|
Sign up to set email alerts
|

Lipo Definition in Thighs: Volumizing and Defining the Vastus Muscles by Fat Transfer

Abstract: Background: Volumizing muscles in the thighs by fat grafting to complement body contouring surgeries has not been adequately investigated. Our objective was to describe a technique (VDVFAT) that defines and volumizes thigh muscles by lipotransfer in the vastus medialis and vastus lateralis muscles. Methods: VDVFAT was performed in 52 patients by the same surgeon at a private clinic in Lima, Peru, between 2018 and 2019. All patients were aged between 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Regarding vascularization of the ESMs, provided by branches of the intercostal and lumbar arteries, the vessels in this region have a smaller caliber; hence, the risk of injury and thromboembolism is lower. 10,28,29 During follow-up, no changes were observed in muscle function, deformities, or asymmetries in the muscle groups under treatment (Figs. 3-6).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Regarding vascularization of the ESMs, provided by branches of the intercostal and lumbar arteries, the vessels in this region have a smaller caliber; hence, the risk of injury and thromboembolism is lower. 10,28,29 During follow-up, no changes were observed in muscle function, deformities, or asymmetries in the muscle groups under treatment (Figs. 3-6).…”
Section: Discussionmentioning
confidence: 96%
“…Regarding vascularization of the ESMs, provided by branches of the intercostal and lumbar arteries, the vessels in this region have a smaller caliber; hence, the risk of injury and thromboembolism is lower. 10 , 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When enhancing the profile view, we should also aim at a harmonic transition between the hip and thigh (lower body profile), which can be achieved by extracting fat from this region or using the volumizing and defining vastus with intramascular fat grafting (VDVFAT) procedure for volumizing the upper vastus lateralis muscle. 13 In the lower body profile, we should aim at a harmonic transition between the gluteal region and the posterior thigh, for which we propose the Hv-FAT procedure (Figs. 5 and 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fat grafting is being increasingly used to volumize muscle groups, especially as a complement to body contouring surgery, styling, and highlighting with liposuction results and few adverse events. [8][9][10][11][12][13][18][19][20][21] The results showed that the increase of the thickness in the immediate postoperative period is evident and 1-month follow-up ultrasound measurements highlighted a decrease in the muscle thickness in relation to the immediate postoperative period in all fat-grafted muscle groups (long head of the biceps femoris and semitendinosus muscles), bilaterally. Nevertheless, despite these results, the patients maintained a good distribution of muscle thickness 1 month after surgery, and this decrease is minimal when compared with the thickness initially obtained after fat grafting, which suggest that the results are possibly sustainable over time (Table 4).…”
Section: Discussionmentioning
confidence: 99%